Electricity from wave and tide : an introduction to marine energy - Lynn, Paul A. (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2014)
"A concise yet technically authoritative overview of modern marine energy devices with the goal of sustainable electricity generation With 165 full-colour illustrations and photographs of devices at an advanced stage, the book provides inspiring case studies of today's most promising marine energy devices and developments, including full-scale grid-connected prototypes tested in sea conditions. It also covers the European Marine Energy Centre (EMEC) in Orkney, Scotland, where many of the devices are assessed. Topics discussed: global resources - drawing energy from the World's waves and tides history of wave and tidal stream systems theoretical background to modern developments conversion of marine energy into grid electricity modern wave energy converters and tidal stream energy converters This book is aimed at a wide readership including professionals, policy makers and employees in the energy sector needing an introduction to marine energy. Its descriptive style and technical level will also appeal to students of renewable energy, and the growing number of people who wish to understand how marine devices can contribute to carbon-free electricity generation in the 21st century"--
"This book introduces all relevant topics in wind and tidal energy from global resources and historical background to today's wave and tidal machines"--
3.6.2 Intermittency and variability3.6.3 Capacity credit and backup generation; References; Chapter 4 Case studies: Wave energy converters; 4.1 Introductory; 4.2 Case studies; 4.2.1 Pelamis; 4.2.2 Oyster; 4.2.3 Limpet and Mutriku; 4.2.4 Wave Dragon; 4.2.5 PowerBuoy®; 4.2.6 Penguin; References; Chapter 5 Case studies: Tidal stream energy converters; 5.1 Introductory; 5.2 Case studies; 5.2.1 Andritz Hydro Hammerfest; 5.2.2 Atlantis Resources; 5.2.3 Marine Current Turbines; 5.2.4 OpenHydro; 5.2.5 Pulse Tidal; 5.2.6 Scotrenewables Tidal Power; 5.2.7 Tidal Generation; References; Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Tidal power-plants.; Ocean wave power; Tidal power; Ocean wave power; Tidal power; TECHNOLOGY & ENGINEERING -- Power Resources -- General; Ocean wave power; Tidal power; Tidal power-plants.; Electronic books